Optimizing Academic Supervision to Improve Teacher Performance at SD Negeri 2 Tempuranduwur - Hari Nugroho; Rejokirono Rejokirono; Didi Supriadi (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to analyze the optimization of academic supervision in improving teacher performance at SD Negeri 2 Tempuranduwur. Using a qualitative descriptive approach, the study explored the planning, implementation, and follow-up processes of academic supervision conducted by the principal, as well as their impact on teachers’ professional performance. Data were collected through interviews, observations, and documentation involving the principal and teachers as research participants. The findings indicate that academic supervision was implemented systematically through supervision planning, classroom observations, reflective feedback, and continuous mentoring activities. The supervision process fostered a collaborative and supportive professional environment that encouraged teachers to improve their instructional practices. As a result, significant improvements were observed in lesson planning, classroom instruction, classroom management, assessment practices, professional motivation, and reflective teaching. The study also found that constructive communication and trust between the principal and teachers contributed substantially to the effectiveness of supervision activities. Although challenges such as limited time and varying levels of teacher readiness were encountered, academic supervision remained an effective strategy for enhancing teacher professionalism and instructional quality. Therefore, optimizing academic supervision can serve as a sustainable approach to improving teacher performance and supporting overall school quality improvement at SD Negeri 2 Tempuranduwur.